Cost of an urban rail ride: A nation-level analysis of ridership, capital costs and cost-effectiveness performance of urban rail transit projects in China - Jinbao Zhao; Chaosu Li; Ruhua Zhang; Mathew Palmer (Journal of Transport and Land Use)
Although urban rain transit (URT) is an attractive alternative mode of daily travel, barriers exist in URT development across the world, in particular, the high cost of construction and operation and relative low rates of URT ridership. Despite these barriers, URT has gained considerable popularity worldwide in recent years; much of this trend is driven by projects in China. Despite this public support and implementation of URT projects, the ridership, capital costs and cost-effectiveness of URT projects remain largely unstudied. This paper addresses this planning and policy issue by examining line-level ridership and investment data for 97 heavy rail transit (HRT) lines and 12 light rail transit (LRT) lines in 28 Chinese cities. Comparative analysis is conducted so as to evaluate the performance and cost-effectiveness of HRT and LRT. Multiple linear regression analysis is used to explain the variability of URT cost-effectiveness and how it varies depending on land use density, project design, system service, and multimodal transit integration. Findings indicate that land-use density, line length, number of transfer stations, operation time, and bus ridership significantly contribute to higher levels of URT ridership, while URT ridership decreases significantly with train headway and the station’s distance from the city center. It is cost-effective to develop URT in high-density cities in spite of high costs, and some, if not all, LRT lines are more cost-effective than HRT lines. As of this analysis, the overdevelopment of HRT in China has failed to plan for multimodal transport integration and operational optimization. However, these shortcomings are also opportunities for Chinese transportation and land-use planners to develop more cost-effective URT projects that also improve the level of service available to the public.